Recurrence patterns predict survival after resection of colorectal liver metastases. Issue 9 (6th June 2022) - Wong, Geoffrey Yuet Mun; Mol, Barend; Bhimani, Nazim; de Reuver, Philip; Diakos, Connie; Molloy, Mark P.; Hugh, Thomas J.
Abstract: Background: Effective treatment of colorectal liver metastases (CRLM) is challenging because recurrence occurs in many patients after curative‐intent resection. This study evaluates the recurrence patterns after resection of CRLM and its association with survival. Methods: A retrospective review of prospectively collected data of patients with CRLM managed with curative‐intent resection from January 2007 to December 2017 was performed. The main outcomes and measures were the timing of recurrence, initial sites of recurrence, overall survival and recurrence‐free survival. Early recurrence was defined as the detection of any organ recurrence ≤6 months from resection of CRLM. Results: A cohort of 194 patients was included for analysis. After a median follow‐up of 85.3 months, 145 patients (74.7%) were diagnosed with recurrence. The median overall survival was 67.6 months (95% CI 50.4–80.2) and the 5‐year overall survival was 54.1%. After initial recurrence was detected, the median survival was 28.9 months (95% CI 23.6–37.8) months and the 5‐year overall survival was 28.8%. Early recurrence occurred in 58 patients (29.9%). Initial recurrence patterns included: liver only in 53 patients (36.5%), multiple sites in 48 patients (33.1%), lung only in 30 patients (20.7%), and other single extrahepatic sites in 14 patients (9.6%). Early recurrence and initial multi‐site recurrence were independent predictors of worse overall survival for patients who develop recurrence after resection of CLRM. Conclusion: The timing and initial sites of recurrence are prognostic factors in determining survival after curative‐intent resection of CRLM. Abstract : This study evaluates the recurrence patterns after resection of CRLM and its association with survival. A retrospective review of prospectively collected data of patients with CRLM managed with curative‐intent resection from January 2007 to December 2017 was performed. The timing and initial sites of recurrence are prognostic factors in determining survival after curative‐intent resection of CRLM.